Electrolytic preparation of Iron powder with particle Size Less than 106 pm - H. Abbar, Ali; Y. Abdul-Ridha, Jameel; H. Kareem, Sameer (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Avery large numbers of articles are made by powder metallurgical methods using electrolytically reduced metal powders. Iron powder is one of these powders which play an important role in this field. Its preparation by electrolytic method is economic in comparison with the traditional methods (Atomization and carbonyl processes). An electrochemical cell consisting of two electrodes (stainless steel cathode and iron anode, 99.9%) was used to study the electrolytic preparation of iron powder with particle size less than 106µm directly as powde1y form. Ferrous sulphate electrolyte was used containing sodium chloride as a stabilizing agent. The produced powder was thoroughly washed with an acidified distilled water and absolute ethanol, then dried under an inert atmosphere at 80°C, and classified by screening. Samples of prepared powder were taken to determine their purity by atomic absorption. The effects of current density, metal ion concentration, sodium chloride concentration, PH, and electrolysis time on the weight percent of iron powder less than (106µm), yield and current efficiency were studied. It was found that an iron powder with particle size less than 106µm can be prepared at a weight percent of iron powder less than I06µm (89.7%) and current efficiency of 71% using cathodic current density of 0.1 A/cm3 and electrolysis time equal to 1 hr. The prepared powder having an apparent density of (3.24 gm/cm3 and real density of 7.39 gm/cm3 with specific surface area of 238 X 103 cm2/gm. Its average particle size was 75 pm and its purity was 99.14%